Distinct stage-wise environmental energy harvesting behaviors within solar-driven interfacial water evaporation coupled with convective airflow. (March 2023) - Zhang, Chenlin; Shi, Yusuf; Wang, Wenbin; Li, Hongxia; Li, Renyuan; Hong, Seunghyun; Wang, Peng
Abstract: Coupling solar-driven interfacial water evaporation with convective airflow (SIWEC) can lead to significantly improved water evaporation performance due to the enhanced environmental energy harvesting. However, the accurate environmental energy harvesting behaviors in such systems have not been thoroughly explored, leading to often vastly different evaporation performances in the literatures un-reconciled. Here, we present a general experimental and computational framework which allows for a fine investigation on the environmental energy harvesting behaviors of SIWEC, for the first time, delineates three distinct stages of environmental energy harvesting behaviors within SIWEC, and further reveals that the amount of harvestable environmental energy within SIWEC has a moderate maximum. The results of this work highlight the critical size-performance relationship of SIWEC, reconcile many seemingly contradicting performances in the literatures, and help set up a reasonable expectation on the environmental energy harvesting by similar systems in practical applications. Graphical Abstract: ga1 Highlights: A general framework allows for a fine investigation on environmental energy harvesting behaviors inside SIWEC was developed. Three distinct stages of environmental energy harvesting behaviors within SIWEC were delineated. The amount of harvestable environmental energy within SIWEC was further revealed. The critical size-performance relationship of SIWEC helps set up a reasonable expectation on environmental energy harvesting in practical application.